THE CORRELATION BETWEEN READING COMPREHENSION AND WRITING ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 MUARO SENTAJO TELUK KUANTAN IN RECOUNT TEXTS - Mailis Mailis; Syofia Delfi; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research is to find out the level of students’ ability in reading comprehension and writing ability in recount texts and the correlation between those variables of the second year students of SMAN 1 Muaro Sentajo. The sample of this research was class XI IPS 2 which consist 25 students. The data were collected by using two kinds of test, reading comprehension and written test. The result of this research showed that the students got good level with the average score 73.28 in reading comprehension, and in writing the students got good level with the average score 76.12. The result of this research proved that there is a positive correlation between reading comprehension and writing ability on recount texts. The rxy distribution of coefficient correlation is 0.8. It means that the correlation was in a high level. So, Ha (alternative hypothesis) of this research is accepted, and null hypothesis (Ho) is rejected. Is there any difference between students’ reading and writing score? So, the researcher try to find out students’ reading and writing score and their correlation. Finally, the researcher suggests for the teacher, they should have some efforts to develop the students’ motivation and encourage them to practice their reading comprehension and writing ability in recount texts.Key words: Correlation, Reading Comprehension, Writing Ability, Recount Texts